Good is up—spatial metaphors in action observation - Gottwald, Janna M.; Elsner, Birgit; Pollatos, Olga (Frontiers in Psychology, 2015)
Positive objects or actions are associated with physical highness, whereas negative objects or actions are related to physical lowness. Previous research suggests that metaphorical connection (“good is up” or “bad is down”) between spatial experience and evaluation of objects is grounded in actual experience with the body. Prior studies investigated effects of spatial metaphors with respect to verticality of either static objects or self-performed actions. By presenting videos of object placements, the current three experiments combined vertically-located stimuli with observation of vertically-directed actions. As expected, participants’ ratings of emotionally-neutral objects were systematically influenced by the observed vertical positioning, that is, ratings were more positive for objects that were observed being placed up as compared to down. Moreover, effects were slightly more pronounced for “bad is down”, because only the observed downward, but not the upward, action led to different ratings as compared to a medium-positioned action. Last, some ratings were even affected by observing only the upward/downward action, without seeing the final vertical placement of the object. Thus, both, a combination of observing a vertically-directed action and seeing a vertically-located object, and observing a vertically-directed action alone, affected participants’ evaluation of emotional valence of the involved object. The present findings expand the relevance of spatial metaphors to action observation, thereby giving new impetus to embodied-cognition research.